Modeling Stock Yield Reaction to Environmental Changes: Does Geopolitical Risk Matter? A VECM Framework in China - Elain, Mohammad I.; AlSabah, Mariam; Al Saber, Ahmad; Pan, Jiazhu; Ali, Mohammed; Boresli, Naser (International Journal of Energy Economics and Policy, 2026)
This paper examines the impact of air pollution on stock market performance, emphasizing geopolitical risk as a mediator. It explores how air pollution's health effects disrupt investor behavior and financial market dynamics, with geopolitical risk bridging the relationship between air quality, emissions policies, and stock performance, thus highlighting the interplay between environmental and financial systems. This study employs the Vector Error Correction Model (VECM) to analyze both short-term and long-term dynamics among the regressors. Using updated data from A-share listed firms on the Shanghai Composite Index, covering the period 2012–2021, the analysis is supported by rigorous stationarity and cointegration tests to ensure the robustness and reliability of the findings. The long-term results indicate that air pollution and geopolitical risk significantly influence stock yield volatility, with deviations from equilibrium gradually corrected over time. In the short term, there is a significant Granger causality between stock yield and both air pollution and geopolitical risk, highlighting their combined impact on stock market performance. The study shows that air quality index negatively affects stock yield by depressing investor sentiment and driving irrational behaviors, emphasizing its role as both a social challenge and a key driver of financial market stability and economic development.